In Burundi, God Becomes a Child a Journey (Journal of Parents and Teachers, 2024)
The article is about the village of Burundi, where every birth is a moment of celebration of life, even though it brings with it fears and insecurities for some children living in remote villages without family or resources. Additionally, the article contains inspiring phrases with deep meaning